Efficacy of Haridradwayadi Rasakriyanjana in Shushkakshipaka w.s.r to Dry Eye Syndrome- A Case Report (International Journal of Ayurveda and Pharma Research, 2021)
Tear secretion is an integral component of the ocular surface physiology; when compromised (quantitatively or qualitatively) lead to Dry eye syndrome with several ocular symptoms and ultimately the patient may end up in corneal blindness. The symptoms of Dry eye syndrome are similar to the disease Shushkakshipaka (ocular surface inflammatory syndrome) in Ayurveda. Vata & Pitta vitiation as per Ayurveda viewpoint are the major contributing pathological factors in its manifestation. Although a number of researches have been carried out and are still continuing, no curative treatment has been achieved yet. This paper aims to establish the efficacy of Haridradwayadi Rasakriyanjana during the clinical observation of a 55 years old female subject who was diagnosed with Shushkakshipaka. She was administered with the drug Haridradwayadi Ghrita in the form of Rasakriyanjana (semi-solid collyrium) drops topically for 30 days, by using subjective and objective assessment criteria which showed a significant result. After the treatment, majority of the symptoms reduced considerably and during the follow up concluded that there was no aggravation of the same.